Tailward Propagation of Magnetic Energy Density Variations With Respect to Substorm Onset Times. Issue 6 (15th June 2018) - Coxon, John C.; Freeman, Mervyn P.; Jackman, Caitriona M.; Forsyth, Colin; Rae, I. Jonathan; Fear, Robert C.
Abstract: During geomagnetic substorms, around 10 15  J of energy is extracted from the solar wind and processed by the Earth's magnetosphere. Prior to the onset of substorm expansion phases, this energy is thought to be largely stored as an increase in the magnetic field in the magnetotail lobes. However, how, when, and where this energy is stored and released within the magnetotail is unclear. Using data from the Cluster spacecraft and substorm onsets from Substorm Onsets and Phases from Indices of the Electrojet (SOPHIE), we examine the variation in the lobe magnetic energy density with respect to substorm onset for 541 isolated onsets. Based on a cross‐correlation analysis and a simple model, we deduce the following: On average, the magnetic energy density increases approximately linearly in the hour preceding onset and decreases at a similar rate after onset. The timing and magnitude of these changes varies with downtail distance, with observations from the mid‐tail ( X ≾ − 9 R E ) showing larger changes in the magnetic energy density that occur ∼20 min after changes in the near‐tail ( X ≿ − 9 R E ). The decrease in energy density in the near‐tail region is observed before the ground onset identified by SOPHIE, implying that the substorm is driven from the magnetotail and propagates into the ionosphere. The implication of these results is that energy in the near‐tail region is released first during the substorm expansion phase, with energy conversion propagating away from the Earth with time. Key Points: Lobe magnetic energy density increases prior to substorms and decreases following onset The change in magnetic energy density is first seen within 9 R E and then propagates downtail On average, the decrease in near‐tail energy density is observed before the ground onset